Enhanced reduction in threading dislocation density in Ge grown on porous silicon during annealing due to porous buffer reconstruction. Issue 1 (6th October 2015) - Calabrese, G.; Baricordi, S.; Bernardoni, P.; De Salvador, D.; Ferroni, M.; Guidi, V.; Morandi, V.; Vincenzi, D.
Abstract : We investigated the effect of annealing on the crystalline quality of Ge epilayers grown on low porosity porous silicon (pSi) buffer layer and on bulk Si by LEPECVD. High‐resolution XRD analysis indicates that during annealing, Ge grown on pSi undergoes a stronger reorganization compared to Ge grown on Si in terms of strain distribution and mosaic broadening. Strong morphological reorganization of the pSi buffer during annealing leads to a stronger reduction in Ge mosaicity as compared to annealed Ge on bulk Si. This improvement is attributed to bending of threading dislocations in a plane parallel to the growth interface, which is attributed to a strain field introduced by pSi within Ge during their simultaneous reorganization at high‐temperature. After cyclic annealing at 750 °C, plan view transmission electron microscopy analysis revealed a threading dislocation density for Ge on pSi which is about one order of magnitude smaller than for annealed Ge on bulk Si. Ge on pSi virtual substrates thus represent a promising platform for the growth of III–V and GeSn semiconductors on Si with a low cost and high‐throughput technique.